2019
DOI: 10.1111/jan.14130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work practice environment, work engagement and work pressure on turnover intention among community health nurses: Mediated moderation model

Abstract: Aim To test the relationship between work practice environment and turnover intention, considering the mediation of work engagement and the moderation of work pressure among community health nurses. Design and Samples A cross‐sectional survey design. Methods A total of 410 nurses were recruited from 32 community health centres between September 2016–January 2017 with survey on work practice environment, work engagement, work pressure and turnover intention. Structural equation modelling was used to test a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
59
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 37 publications
9
59
3
6
Order By: Relevance
“…The instrument's mean score showed to be lower than that of studies that evaluated the practice in countries like the United States, China, and Turkey (14)(15)(16) .…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The instrument's mean score showed to be lower than that of studies that evaluated the practice in countries like the United States, China, and Turkey (14)(15)(16) .…”
Section: Discussioncontrasting
confidence: 59%
“…On the other hand, a national research study carried out in hospitals similar to the one in this study, that is, a public and teaching one, has revealed similar results to the ones presented here (20) . We highlight with regret that, in the Brazilian scenario, although we have only one research study published until now considering the whole hospital, the environment's characteristics of the hospitals funded by the Unified Health System (Sistema Único de Saúde, SUS) are more precarious when compared to those of the private hospitals (20) and, also, to the international literature (14)(15)21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such positive effects can also be expected when CI is implemented with the explicit aim to improve employees' working conditions [34,37]. Lower job demands, and in this dynamic task environment, lower stress, as well as related higher work engagement, are of particular importance given the contemporary concerns about the consequences of nurses' high workloads [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%